Mechanistic studies of the anti-ulcerogenic activity and acute toxicity evaluation of dichlorido-copper(II)-4-(2-5-Bromobenzylideneamino)ethyl) piperazin-1-ium phenolate complex against ethanol-induced gastric injury in rats - Salga, M.S.; Hadi, A.H.A.; Hussain, P.D.; Abdelwahab, S.I.; Abdullah, M.A.; Ali, Hapipah Mohd (2011)
The compound dichlorido-copper(II)-4-(2-5-bromobenzylideneamino)ethyl) piperazin-1-ium phenolate (CuLBS) was synthesized, characterized and screened for acute toxicity and protective activity against ethanol-induced gastric mucosal injury in rats. Gross microscopic lesions, biochemical and immunological parameters and histochemcial staining of glycogen storage were taken into consideration. Oral administration of CuLBS (30 and 60 mg/Kg) for two weeks dose-dependently flattened gastric mucosa, significantly increased gastric mucus and total acidity, compared with control group (P < 0.01). Serum levels of liver enzymes aspartate (AST) and alanine transaminases (ALT), pro-inflammatory (IL-6 and TNF-alpha) and anti-inflammatory (IL-10) cytokines in the rats exposed to ethanol induced ulceration have been altered. Administration of CuLBS showed considerable (P < 0.05) protection against ulceration by modulating the acute alterations of cytokines AST, ALT and stomach glycogen. Interestingly, CuLBS did not interfere with the natural release of nitric oxide. CuLBS alone (60 mg/Kg) did not exhibit any ulcerogenic effect as assessed using Adami's scoring scale. An acute toxicity study showed that rats treated with CuLBS (1,000 and 2,000 mg/Kg) manifested no abnormal signs. These findings therefore, suggested that the gastroprotective activity of CuLBS might contribute in modulating the inflammatory cytokine-mediated oxidative damage to gastric mucosa.